Meldecieuse Bakery / Shazlinda Atirah Nordin - Shazlinda Atirah, Nordin (2020)
Meldecieuse Bakery offers pastries and bread products and services for our customers. Our company providing the variety type of cake, muffin, cupcake, tart and etc. Since our business is a cafe that providing drive-thru, our company also providing a few type of beverage which are belgian chocolate drinks, coffee and fruit juice and our instant mixing cake flour product that gives satisfaction of consumer. Meldecieuse Bakery is a start-up bakery cafe to be established in Ipoh, Perak. We would like to attract our customer to interest with our products with variety pastry, cookies, bread and drinks with our drive-thru facilities which can save customers time without having to leave their vehicles. Ipoh is a capital town in Perak which is a strategies place to set up a new business because there are many attractions from the government and private sectors. The company plans to build a strong market position in the town, due to our aims to offers a products with competitive prices to meet the demands of the low to medium income locals and tourists. Meldecieuse Bakery marketing strategy is to emphasize the quality and price of our services and product. Our company offer the affordable price because not people can afford to buy expensive things and not every people who lives in Ipoh gain a big income. Thus, our company develop marketing strategy that can attract people to come to our cafe and taste our product especially for poor people. The management of Meldecieuse Bakery consists of two partners which is the general manager Shazlinda Atirah Binti Nordin and her partners Shahira Azira Binti Nordin which in financial manager position. In addition, our workers has extensive experience in, business, financial, marketing and sales. Lastly, Meldecieuse Bakery have service and products commitments plan to aggressively build our brand through newspaper, ads, radio, internet and banners. The drive-thru bakery cafe Meldecieuse Bakery is a No.1 bakery in Malaysia that provide drive-thru services other than fast food restaurant such as Mc Donalds and KFC.